Role of glycoproteins in hepatic lipid metabolism: emerging diagnostic markers and therapeutic targets - Bo Lan; Sixing Huang; Jinping Luo; Ping Shi; Zhe Qiang (PeerJ, 2025)
The liver is an important metabolic organ in the human body, and abnormal hepatic lipid metabolism may lead to a variety of diseases such as metabolic dysfunction-associated fatty liver disease, cirrhosis, and hepatocellular carcinoma. These diseases are often closely associated with chronic diseases, including obesity, hypertension, high cholesterol and diabetes, and have become major factors increasing the global disease burden. Currently, the diagnosis of diseases related to hepatic lipid metabolism relies mainly on imaging findings and serologic markers. In terms of treatment, lifestyle interventions such as dietary changes and increased exercise remain the mainstay of the fight against the diseases. However, effective therapies to control the progression of these diseases are still lacking. Glycoproteins are complex biomolecules consisting of sugar chains and proteins bound covalently, which are widely found in cell membranes and secretory fluids. In recent years, researchers have found that glycoproteins have potential application value in the diagnosis and treatment of diseases related to hepatic lipid metabolism. But there are currently no articles summarizing and analyzing the pathways and mechanisms involved. This review provides an overview of the progress of research on glycoproteins involved in diseases related to hepatic lipid metabolism as well as new insights into glycoproteins as potential diagnostic markers and therapeutic targets for lipid metabolism diseases.